Report of Health Week Committee
1924-02-25 1924 1920s 4 pages HEALTH WEEK, 1923. STATEMENT OF INCOME AND EXPENDITURE. Expenditure. Income. £ s. d. £ s. d. Printing 60 18 5 Balance from 1922 Postage 19 10 3 Donations- Sundry Expenses 0 18 9 British Commercial Gas Asso. 100 0 0 Press Propaganda 50 0 0 Kent Insurance Committee 3 8 0 School Prizes 25 0 0 The Rt. Hon. T. R. Ferens 10 0 0 Contribution towards organising Ex- Royal Liver Friendly Society. 2 2 0 penses incurred by the R.S.I. 25 0 0 National Mutual Life Assur- Balance of Income over Expenditure 5 13 4 ance Society 10 0 0 Refuge Assurance Co., Ltd 21 0 0 Guardian Assurance Co., Ltd. 5 5 0 London and Manchester As- surance Co., Ltd. 10 10 0 Chadwick Trust 10 10 0 Sale of Literature £187 0 9 3 [Table on the right-hand side, containing sub-totals] £ s. d. 4 4 9 172 10 0 10 6 0 £187 0 9 292/842/1/10